Fundamentals of condensed matter and crystalline physics : an introduction for students of physics and materials science - Sidebottom, David L., 1961- (New York : Cambridge University Press, 2012)
'This undergraduate textbook merges traditional solid state physics with contemporary condensed matter physics, providing an up-to-date introduction to the major concepts that form the foundations of condensed materials. The main foundational principles are emphasized, providing students with the knowledge beginners in the field should understand. The book is structured in four parts and allows students to appreciate how the concepts in this broad area build upon each other to produce a cohesive whole as they work through the chapters. Illustrations work closely with the text to convey concepts and ideas visually, enhancing student understanding of difficult material, and end-of-chapter exercises varying in difficulty allow students to put into practice the theory they have covered in each chapter and reinforce new concepts'--
Part I. Structure: 1. Crystal structure; 2. Amorphous structure; 3. Bonds and cohesion; 4. Magnetic structure -- Part II. Scattering: 5. Scattering theory; 6. Scattering by crystals; 7. Scattering by amorphous matter; 8. Self-similar structures and liquid crystals -- Part III. Dynamics: 9. Liquid dynamics; 10. Crystal vibrations; 11. Thermal properties; 12. Electrons: the free electron model; 13. Electrons: band theory; 14. Bulk dynamics and response -- Part IV. Transitions: 15. Introduction to phase transitions; 16. Percolation theory; 17. Mean field theory and renormalization; 18. Superconductivity; Appendices.
Includes bibliographical references (pages 390-393) and index.
Keywords: Condensed matter -- Textbooks; Crystals -- Textbooks